Fecal Microbiota Transplantation for Patients With Irritable Bowel Syndrome: A Meta-Analysis of Randomized Controlled Trials - Zhao, Hui-jun; Zhang, Xiao-jing; Zhang, Na-na; Yan, Bin; Xu, Ke-ke; Peng, Li-hua; Pan, Fei (Frontiers in Nutrition, 2022)
Background: Gut microbiota has been identified as an imbalance in patients with irritable bowel syndrome (IBS). Fecal microbiota transplantation (FMT) is a novel method to restore microbiota and treat IBS patients. Objective To conduct a meta-analysis and estimate the efficacy and safety of FMT for the treatment of IBS patients with subgroup analyses to explore the most effective way of FMT for IBS. Methods All eligible studies were searched from PubMed, Embase, Web of Science, and the Cochrane Library through multiple search strategies. Data were extracted from studies comprising the following criteria: double-blind, randomized controlled trials (RCTs) that compared the efficacy of FMT with placebo for adult patients (≥18 years old) with IBS. A meta-analysis was performed to evaluate the summary relative risk (RR) and 95% confidence intervals (CIs). Results A total of seven RCTs comprising 489 subjects were eligible for this meta-analysis. Pooled data showed no significant improvement of global IBS symptoms in patients with FMT compared with placebo (RR = 1.34; 95% CI 0.75–2.41, p = 0.32). A significant heterogeneity was observed among the studies (I2 = 83%, p < 0.00001). There was no significant evidence of funnel plot asymmetry (Egger's test, p = 0.719; Begg's test, p = 1.000), indicating no existence of publication bias. Subgroup analyses revealed that FMT operated by invasive routes, including gastroscope, colonoscope, and nasojejunal tube, significantly improved global IBS symptoms (RR = 1.96; 95% CI 1.23–3.11, p = 0.004) with heterogeneity (I2 = 57%, p = 0.06) and an NNT of 3 (95% CI 2–14). However, FMT delivered via oral capsules showed a negative impact on patients with IBS (RR = 0.56; 95% CI 0.33–0.96, p = 0.03) with a low heterogeneity (I2 = 39%, p = 0.2) and an NNH of 3 (95% CI 2–37). Conclusion The current evidence from RCTs with all routes of FMT does not show significant global improvement in patients with IBS. However, FMT operated by invasive routes significantly improved global IBS symptoms.